Rancang Bangun Prototipe Alat Keamanan Penjarahan pada Truk Bermuatan dengan menggunakan Sensor Pir Berbasis Arduino dan IoT - Nabil Angger Pradana; Eddy Nurraharjo (KITA Institute, 2023)
Looting is a serious crime that threatens the safety and integrity of the truck's cargo, which can lead to financial loss and even threaten the safety of the driver and crew. To overcome this problem, this study focuses on developing a theft warning system using advances in Internet of Things (IoT) technology and smart devices. The prototype was built using a highly sensitive PIR sensor as a motion detector around the truck. The data from the PIR sensor is then processed by the Arduino Uno, which acts as the brains of the system, and through the HC-05 Bluetooth connection, alarm and vibration messages are transmitted to the user's smartphone drive. This allows drivers to react quickly and be on the lookout for or notify authorities of the possibility of looting. With the successful development of this alarm system, it is hoped that it can improve the level of security in the trucking industry and reduce the risk of cargo loss due to looting. Moreover, the success of this study also has a positive contribution to the application of IoT technology to improve safety in the field of transportation and logistics.